At the swimming pool - Read, Leon; Crawford, Andy (London Franklin Watts, 2008)
Very young readers will enjoy this introduction to the swimming pool
Scientific notions
1
Keywords: Swimming -- Juvenile literature; Swimming pools -- Juvenile literature; Swimming